PENGARUH BUDAYA ORGANISASI DAN KOMPETENSI TERHADAP KINERJA PEGAWAI DAN GURU PADA SMP NEGERI 14 KOTA LUBUKLINGGAU - Irma Idayati; Anggun Asparingga (LPPM UNIVERSITAS BINA INSAN, 2017)
This study aims to describe the magnitude of the influence of organizational culture and competence on the performance of employees and teachers in SMP Negeri 14 Lubuklinggau City. In this study using primary and secondary data sources, namely data collected by authors from books and literature that are relevant to leadership functions. The results showed that there was a significant effect of organizational culture and competency together on the performance of employees and teachers in Lubuklinggau City 14 Middle School, this was evidenced by the results of the calculation obtained that the calculated value was = 7.660 greater than the value of ftabel = 3.21 and the probability (sig. 0,000) is smaller or less than 0.05, so Ha: Accepted and H0: Rejected, and means that there is a significant influence of organizational culture and competency together on the performance of employees and teachers in SMP Negeri 14 Kota Lubuklinggau . From the calculation results of processing respondents' answers to organizational culture, employees and teachers must have a high awareness in working, developing themselves and obeying the rules, having a polite personality, setting work plans before doing work. In addition, employees and teachers in doing work need peace. Then competencies, employees and teachers must attend training to be able to improve their knowledge, must have special expertise in carrying out their work, have a polite, friendly, polite and responsible attitude to the work given to him.